Emerging personality in adolescence: developmental trajectories, internalizing and externalizing problems, and the role of mentalizing abilities. Issue 3 (23rd December 2022) - Benzi, Ilaria Maria Antonietta; Fontana, Andrea; Barone, Lavinia; Preti, Emanuele; Parolin, Laura; Ensink, Karin
Abstract: Introduction: Identifying longitudinal trajectories of emerging personality (EP) is crucial to highlight developmental patterns that might foster personality pathology in adolescence and early adulthood. Research on the exacerbation of personality pathology in adolescence identifies the significant contribution of internalizing and externalizing problems and suggests the importance of considering aspects such as mentalization, while accounting for gender differences. Methods: In our study, we adopted a mixed‐model approach to (1) explore longitudinally EP (Adolescent Personality Structure Questionnaire; APS‐Q) over 12 months in a sample of adolescents ( N = 178, 62% females, mAGE = 15.04, SD = 1.27), accounting for gender effects. Moreover, (2) we assessed the longitudinal effect of internalizing and externalizing problems (Youth Self‐Report; YSR‐112) on EP. Finally, (3) we addressed the moderating role of mentalization (Movie Assessment for Social Cognition; MASC) in this developmental pathway. Results: Results highlighted a two‐way pattern of EP. No changes were found in the level of difficulties in Self‐acceptance, Investments and Goals, and Relationships with family dimensions. However, significant changes were found in personality functioning in the dimensions of Sense of Self, Aggression, and Relationships with friends. More, changes in difficulties in Sexuality emerged only in females. Also, gender differences emerged in the level of severity of EP. In addition, Internalizing and Externalizing problems differentially predicted difficulties in personality dimensions. Finally, mentalizing features moderated the relationship between Internalizing problems and Sense of Self and Internalizing problems and Self‐acceptance, respectively. Conclusions: Our contribution aligns with recent developmental models of personality pathology, suggesting that different personality dimensions develop at different paces. More, it highlights the predictive power of externalizing and internalizing problems on difficulties in personality dimensions. Finally, it advances the discussion on the contribution of mentalizing abilities to EP.